DEVELOPMENT AND VALIDATION OF RP-HPLC METHOD FOR DETERMINATION OF FLUINDIONE AND ITS THREE INHERENT IMPURITIES IN PHARMACEUTICAL DOSAGE FORMS (International Journal of Food and Nutritional Sciences, 2022)
A reversed-phase high-performance liquid chromatography (RP-HPLC) method was developed and validated for the identification and quantification of Fluindione and its three inherent related substances in finished dosage forms. Chromatographic separation was achieved on an Ascentis Column (150 mm x 4.6mm, 2.7m) with the mobile phase (0.1% Ortho Phosphoric acid as buffer and Acetonitrile in gradient mode. The HPLC flow rate was 1.0 ml/ min and peaks were monitored at 226 nm using a UV detector.